STUDY ON THE FISHERY AND BIOLOGY OF THE MANTIS SHRIMP ORATOSQUILLA NEPA (LATREILLE) OF SOUTH KANARA COAST DURING 1979-83 - Sukumaran, K K (Indian Journal of Fisheries, 2011)
The catches of Oratosquilla nepa along the South Kanara coast were maximumduring 1981-82, amounting to 2543.3 t at a catch rate of 16.5 kg|h at Mangaloreand to 1868.8 t at 16.7 kg|h at Malpe. The catch was high during January-April. A mean growth of 7-8 mm|month was indicated. The species appear togrow to it length of about 108 mm by the end of first year and to live for 15-16months. In the development of the ovary, five maturity stages, ie., immature, earlymaturing, late maturing, mature and spent|spent-recovering, have been recognised.The size at maturity at 50% level is estimated at 95 mm. The spawning seasonis found to be extending from December to October with peaks during March-Juneand September-October. Females generally outnumbered males. Chi-square testshowed significant variation from 1:1 ratio in the distribution of sexes. The fecundityis estimated at 6,78,200 in a female measuring 108 mm body length. Thegrowth parameters, 1 a, and c.k were estimated at 143 mm and 0.2877 respectively.The mean.monthly Z values were 0.9767 for males and 0.923d for females